Carbon Footprint for Industry -Al-Rasheed Vegetable Oil Factory - Elham M. Al-Bayati; Jinan S. Al-Hassan (Baghdad Science Journal, 2024)
This is a comprehensive study to calculate the carbon footprint of the Al-Rasheed vegetable oil factory in gaining a clear understanding of the environmental impact and identifying opportunities for emission reduction and sustainability improvement and to provide an overview of the key elements and objectives of the current study. Utilizing industry-standard calculation methodologies and emission factors specific to Al-Rasheed Factory and geographic location, we analyzed the collected data to quantify Al-Rasheed carbon emissions across only scope 1(Direct GHG Emissions via the burning of fossil fuels) measured by using the latest IPCC 2021 version 1.02 GHG Protocol and the SimaPro version 9.5 LCA  software was used for modeling the processes analyzed in this study IPCC 2021 with a timeframe of 20 years( GWP100) and by using the conventional emission factor. It is confirmed that calculating carbon footprint applying Sima Pro software is more realistic than using the emission factor conversion equation. The factory consumed a total amount of diesel while it was operational equal to 17472000 liters, which is equivalent to 8,476,837 kg CO2-eq carbon footprint. This is significant amounts of GHG gases emitted to the atmosphere for more than 50 years. Thus, it was concluded that the Al-Rasheed vegetable oil factory is a major source of air pollution for the city Baghdad especially with the fact that it is now located in residential area. Therefore, it is recommended that mitigation measures should be considered seriously when the Al-Rasheed vegetable oil factory will be operational again.